Kinetics of moisture loss during stirring of cheese curds produced from standardised milks of cows on pasture or indoor feeding systems. (20th December 2017) - Panthi, Ram R; Kelly, Alan L; Hennessy, Deirdre; McAuliffe, Stephen; Mateo, Maria; O'Donnell, Colm; O'Callaghan, Donal J; Sheehan, Jeremiah J
Abstract : This study compared the in‐vat moisture loss kinetics under fixed cheesemaking conditions during 75 min of stirring of curds prepared from protein‐standardised milks produced from indoor cows fed total mixed ration (TMR), or outdoor cows fed grass only (GRA) or grass mixed with clover (CLO). Relative curd moisture as a function of time was fitted to different empirical equations, of which a logarithmic function gave the best fit to the experimental data. The moisture loss rate constant (k/min) was found to be similar for curds from protein‐standardised TMR, CLO and GRA milks, showing minimal feed‐induced variations in syneresis.